2004
DOI: 10.1115/1.2055987
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Fueled Spark-Ignition Engines Predictive and Experimental Performance

Abstract: Hydrogen is well recognized as a suitable fuel for spark-ignition engine applications that has many unique attractive features and limitations. It is a fuel that can continue potentially to meet the ever-increasingly stringent regulations for exhaust and greenhouse gas emissions. The application of hydrogen as an engine fuel has been tried over many decades by numerous investigators with varying degrees of success. However, the performance data reported often tend not to display consistent agreement between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…A comparison to experimental results showed good agreement for variation of compression ratio, air-fuel equivalence ratio and intake air temperature [162]. These results suggest that the operating regime of a hydrogen engine is strongly limited by the occurrence of knocking combustion.…”
Section: Autoignitionmentioning
confidence: 51%
See 1 more Smart Citation
“…A comparison to experimental results showed good agreement for variation of compression ratio, air-fuel equivalence ratio and intake air temperature [162]. These results suggest that the operating regime of a hydrogen engine is strongly limited by the occurrence of knocking combustion.…”
Section: Autoignitionmentioning
confidence: 51%
“…Li and Karim use a two-zone quasi-dimensional model with a triangular combustion rate law fitted to experimental data coupled to a chemical kinetic scheme [162]. They propose a knock criterion, comparing the energy released by end-gas reactions to the energy released by the normal flame propagation.…”
Section: Modeling Abnormal Combustion Phenomenamentioning
confidence: 99%
“…Tang et al [1] used lean mixtures at CR of 12.5:1 and 14.5:1 as did Smith et al [15] without occurrence of knock. However Karim et al [16] in experimental and theoretical work indicate wide knocking regions even at CRs as low as 6. It can be concluded that the operational regions of combustion knock depends on a number of engine operation parameters including intake air temperature and intake pressure and will vary for different engine design and configuration.…”
Section: Combustion Knockmentioning
confidence: 95%
“…The drive for the adoption of this technique is supported by a considerable set of advantages. It can be installed easily with only simple modification required (Lee, Yi & Kim, 1995) and the cost is low (Li & Karim, 2006). The flow rate of supplied hydrogen can also be controlled conveniently (Sierens & Verhelst, 2001).…”
Section: Introductionmentioning
confidence: 99%